HAMBATAN GURU PENDIDIKAN JASMANI GENERASI 80-AN DALAM PEMBELAJARAN DARING DI TENGAH PANDEMI COVID-19 - Yahya Eko Nopiyanto (Jurnal Sporta Saintika, 2020)
This study was to describe the obstacles of physical education 80’s generation teacher in online learning in the Covid-19 pandemic. The study was a descriptive quantitative with survey approach. The data were gathered by questionnaire with Likert scale. Subjects of this study were 30 physical education 80’s generation teacher in senior high school in North Bengkulu, Indonesia. The data were analyzed by descriptive percentage. The result of this study showed that physical education 80’s teachers in senior high school experienced obstacles in online learning in the Covid-19 pandemic.